A BOOTSTRAP APPROACH FOR IMPROVING LOGISTIC REGRESSION PERFORMANCE IN IMBALANCED DATA SETS - Chang, Michael; Dalpatadu, Rohan J; Phanord, Dieudonne; Singh, Ashok K (MATTER: International Journal of Science and Technology, 2018)
In an imbalanced dataset with binary response, the percentages of successes and failures are not approximately equal. In many real world situations, majority of the observations are “normal” (i.e., success) with a much smaller fraction of failures. The overall probability of correct classification for extremely imbalanced data sets can be very high but the probability of correctly predicting the minority class can be very low. Consider a fictitious example of a dataset with 1,000,000 observations out of which 999,000 are successes and 1,000 failures. A rule that classifies all observations as successes will have very high accuracy of prediction (99.9%) but the probability of correctly predicting a failure will be 0. In many situations, the cost associated with incorrect prediction of a failure is high, and it is therefore important to improve the prediction accuracy of failures as well. Literature suggests that over-sampling of the minority class with replacement does not necessarily predict the minority class with higher accuracy. In this article, we propose a simple over-sampling method which bootstraps a subset of the minority class, and illustrate the bootstrap over-sampling method with several examples. In each of these examples, an improvement in prediction accuracy is seen.